High-Selective CO2 Capture in Amine-Decorated Al-MOFs - Yinji Wan; Yefan Miao; Ruiqin Zhong; Ruqiang Zou (Nanomaterials, 2022)
Amine-functionalized metal-organic framework (MOF) material is a promising CO2 captor in the post-combustion capture process owing to its large CO2 working capacity as well as high CO2 selectivity and easy regeneration. In this study, an ethylenediamine (ED)-decorated Al-based MOFs (named ED@MOF-520) with a high specific area and permanent porosity are prepared and evaluated to study the adsorption and separation of CO2 from N2. The results show that ED@MOF-520 adsorbent displays a superior CO2 capture performance with a CO2/N2 separation factor of 50 at 273 K, 185% times increase in the CO2/N2 separation efficiency in comparison with blank MOF-520. Furthermore, ED@MOF-520 exhibits a moderate-strength interaction with 29 kJ mol−1 adsorption heat for CO2 uptake, which not only meets the requirement of CO2 adsorption but also has good cycle stability. This work provides a promising adsorbent with a high CO2/N2 separation factor to deal with carbon peak and carbon neutrality.